Getting lost as a way of knowing: the art of boxing within Shape Your Life. Issue 5 (19th October 2016) - van Ingen, Cathy
Abstract: This article unfolds in and through a series of paintings completed and exhibited as part of Shape Your Life, a free, recreational boxing programme for female and trans survivors of violence in Toronto. The paintings were completed by participants on used pieces of canvas from the boxing ring floor at the Toronto Newsgirls Boxing Club, the site of the boxing programme. In these paintings, participants illustrate the significant role that boxing and art can play in making difficult pasts comprehensible, if only in part. In an effort to articulate methodology out of practice, I rely on 'getting lost' as both a methodology and a mode of representation. To that end, the article grapples with experiential verses interpretive authority, and the inclusion of participants' art and voices to reflect the implications of the 'post' for research within sport for development and peace (SDP) programmes. The art also addresses the systemic nature of gender-based violence and the limitations of any SDP programme to wholly respond to individuals' trauma.